Illegal drug use through the lifecourse: a study of 'hidden' older users - Moxon, David (Routledge, 2017)
Introduction -- Methodology -- Past: lives spent with illegal drugs -- Present: living with illegal drugs today -- Future: prospects for hidden illegal drug use among older adults